Bilateral Glaucoma in An Infant with Phacomatosis Pigmentovascularis and Sturge-Weber Syndrome: A Rare Case Report: Doi: 10.36351/pjo.v40i3.1733 - Yulia, Dian Estu; Soeharto, Diajeng Ayesha (Pakistan Journal of Ophthalmology, 2024)
Prevalence of concurrent PhakomatosisPigmentovascularis (PPV)and Sturge-Weber syndrome (SWS)is unknown due to its rarity and sporadic occurrence. In this case report, we present a rare case of bilateral glaucoma in an infant with PPV and SWS. Athree-month old male infant presented with hazy cornea and visible black spots in the upper sclera and presented with intraocular pressure (IOP) of 40 and 52 mmHg in the left and right eye, respectively. Trabeculectomy-Trabeculotomy for both eyes was done which initially decreased IOP. However, high IOP recurred, and the patient was treated with topical medication.At one year follow-up, the patient had normal IOP and was responsive to light and object. Our case is a rare presentation of concurrent SWS, PPV, and bilateral glaucoma. The potential systemic comorbidities of this condition highlights that it is imperative that these patients are diagnosed early, treated promptly, and are monitored periodically.